Queen [compact disc] - Minaj, Nicki (Cash Money/Republic Records, 2018)
Nicki Minaj is back with her fourth studio album, which includes the singles Chun-Li and Rich Sex. it also features the new track Bed, which is a collaboration with Ariana Grande.